MODEL KONSEPTUAL : PENGARUH E-SERVQUAL DAN INTERAKSI MEDIA SOSIAL TERHADAP KEPUASAN PELANGGAN MELALUI CUSTOMER ENGAGEMENT - I Kadek Wira Diana; Kadek Hery Krista Yana; I Gusti Agung Ngurah Bhagat Tenaya; Ni Nyoman Kerti Yasa; Putu Yudi Setiawan (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
Digital transformation has changed the way companies interact with customers. In a digital business environment, customer engagement has become a key factor in building long-term relationships with customers. This conceptual article aims to develop a customer engagement model by integrating E-Servqual and social media interaction with customer satisfaction. Through a literature review approach, this article proposes that E-Servqual has a positive effect on customer engagement, which in turn enhances customer satisfaction. Furthermore, social media interaction has a positive effect on customer engagement and consequently enhances customer satisfaction as well. It is hoped that the proposed model will enrich the literature on digital marketing and consumer behaviour and serve as a foundation for future research. This conceptual model highlights the importance of the roles of E-Servqual and social media interaction in building sustainable customer engagement to enhance customer satisfaction.